2016
DOI: 10.1177/2165143416681288
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Personal Finance Mathematical Problem Solving to Individuals With Moderate Intellectual Disability

Abstract: Managing one's finances is an important milestone toward financial security and responsibility (Bell, Burtless, Gornick, & Smeeding, 2006). In general, the acquisition of academic skills has been found to be significantly related to positive outcomes in adult life (e.g., employment, citizenship, community living,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
(34 reference statements)
2
29
0
2
Order By: Relevance
“…Ten (42%) of the studies included in the review used real-world problems to teach mathematics skills from across all NCTM content standards to students across all grade bands (Browder, Jimenez, Spooner et al, 2012; Browder, Jimenez, & Trela, 2012; Creech-Galloway et al, 2013; Jimenez & Kemmery, 2013; Jimenez & Staples, 2015; Root, Saunders, Spooner, & Brosh, 2017; Spooner et al, 2012). Of the studies that utilized math stories, five (50%) included students with MSD in an elementary setting, three (30%) in a middle school setting, and two (20%) in a high school setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten (42%) of the studies included in the review used real-world problems to teach mathematics skills from across all NCTM content standards to students across all grade bands (Browder, Jimenez, Spooner et al, 2012; Browder, Jimenez, & Trela, 2012; Creech-Galloway et al, 2013; Jimenez & Kemmery, 2013; Jimenez & Staples, 2015; Root, Saunders, Spooner, & Brosh, 2017; Spooner et al, 2012). Of the studies that utilized math stories, five (50%) included students with MSD in an elementary setting, three (30%) in a middle school setting, and two (20%) in a high school setting.…”
Section: Resultsmentioning
confidence: 99%
“…Simulation was evaluated in two (8%) of the studies (Ayres, Langone, Boon, & Norman, 2006; Hansen & Morgan, 2008). Two (8%) studies looked at calculator use (Root, Saunders, et al, 2017; Yakubova & Bouck, 2014), one (4%) evaluated the use of a math game to teach number identification (Everhart, Alber-Morgan, & Park, 2011), one (4%) utilized single-switch voice output devices (Hudson, Zambone, & Brickhouse, 2016), and one (4%) measured generalization from a worksheet to an iDevice (Root, Saunders, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The use of calculators and technology has also been found to be effective for supporting adults with ID to learn mathematics. Root, Saunders, Spooner, and Brosh (2017) conducted 24 one-on-one instructional sessions with three middle school students aged 14 years in a program designed to improve personal finance problem solving skills. The researchers used a variety of tools such as calculators, iDevices, graphic organisers and checklists.…”
Section: Adult Learners With Intellectual Disabilitiesmentioning
confidence: 99%
“…The learning pathway was then designed as ways that -I conjectured -could support the envisioned changes in adults' participation from their starting points to achievement of their goals. This included deliberating whether it would be possible to design tools to support the envisioned forms of participation (Cuskelly & Faragher, 2019;Prendergast et al, 2017;Root et al, 2017). Cortina et al (2019) caution that research design should not be reduced to the designing of tools and tasks to support learning.…”
Section: The Design Research Cyclementioning
confidence: 99%
“…They found that all of the participants showed more improvements when using the TOUCHMATH program over the number line intervention. Root, Saunders, Spooner, and Brosh (2017) evaluated the use of a modified schema-based instructional package that included a student self-instruction sheet, modeltest procedure, and system of least prompts to teach 2-digit real-world word problems.…”
Section: Middle School Academic Instructionmentioning
confidence: 99%